Effectiveness of Msap, Fiscus Services and Taxation Sanctions on Tax Obligation Compliance with Patriotism as Intervening Variables - Ali Sandy Mulya (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2020)
this research is to find out how much influence the modernization of the tax administration system (MSAP), the tax authorities and tax sanctions on tax compliance through patriotism. The population in this study are taxpayers who have registered at the serpong pratama tax service office. The sample in this study amounted to 99 respondents who were selected using a simple random sample (Simple Random Sampling). Data collection method is done by distributing questionnaires for 1 month. Data analysis techniques used in this study used Smart PLS and SPSS software. The tax authorities have a significant effect on taxpayer compliance, while the modernization of the tax administration system and tax sanctions have no significant effect on taxpayer compliance even with patriotism as an intervening variable. although there is a modernization of the tax administration system that has been more but the level of tax authorities is still a cornerstone to increase taxpayer compliance in paying taxes